Housing subsidies and taxation in six EU countries: Trends, structures and recent measures in the light of the global financial crisis. Issue 3 (28th October 2014) - Wieser, Robert; Mundt, Alexis
Abstract : Purpose: – This paper aims to examine the main characteristics of the housing taxation and subsidy systems in six European Union countries. The structure of this support over the past two decades, before and after the global financial crisis has been investigated and its total effective dimensions have been approximated. Design/methodology/approach: – Official national data and existing literature on housing policy expenses have been analysed and the authors add their own estimations of missing data, where possible. Latest changes in housing policy guidelines and expenses were interpreted. Findings: – It was found that state support for housing is heavily underestimated by official data in most countries, mainly due to missing estimates for the value of imputed rents tax relief, reduced VAT rates and low real estate and capital gains taxation. Our estimates suggest that total public support for the housing sector reaches more than 3 per cent of the gross domestic product in three of the six countries, and about 2 per cent in the others. State support to the housing sector has developed quite differently in the investigated countries over the past decades. In particular, there was no universal downward trend. Originality/value: – This is the first attempt to provide a more comprehensive analysis of national housing policy expenses applying a very broad definition of state support for housing. In particular, we consider indirect tax advantages to the housing sector that are generally not taken into account. Furthermore, we apply a discounted present value approach of current housing policy expenses to facilitate international comparison.